The evolution of public attention in acute kidney injury and continuous renal replacement therapy: trends analysis from 2004 to 2024 - Thongprayoon, Charat; Wathanavasin, Wannasit; Suppadungsuk, Supawadee; Sheikh, Mohammad S.; Abdelgadir, Yasir H.; Miao, Jing; Mao, Michael A.; Craici, Iasmina M.; Qureshi, Fawad; Kashani, Kianoush B.; Cheungpasitporn, Wisit (Frontiers in Nephrology, 2024)
BackgroundAcute kidney injury (AKI) and the need for Continuous Renal Replacement Therapy (CRRT) are critically important health concerns. This study analyzes global and regional Internet search queries to understand public attention in AKI and CRRT over time.MethodsWe used Google Trends™ to analyze search queries for AKI and CRRT from January 2004 to March 2024. The study examined global trends and detailed insights from the United States, including state-by-state breakdowns. We identified patterns, peaks of attention, and temporal trends in public attention, comparing regional variations across the US and top-ranking countries worldwide.ResultsGlobal attention in AKI peaked in October 2022, with Portugal, Zambia, and Spain showing the highest regional attention. Within the United States, peak attention was in February 2008. Tennessee, Pennsylvania, and West Virginia were the top states that paid attention to AKI. Attention in CRRT peaked globally in March 2024. South Korea, Saudi Arabia, and Bahrain have led the global attention to CRRT. In the United States, peak attention was in April 2020. West Virginia, Tennessee, and Kentucky showed the highest state-specific attention in CRRT.ConclusionsThis study reveals significant temporal and geographical variations in online search patterns for AKI and CRRT, suggesting evolving public attention to these critical health issues. This knowledge can guide the development of targeted public health initiatives, enhance medical education efforts, and help healthcare systems tailor their approach to improving awareness and outcomes in kidney health across diverse populations.